The Thessalian Mesolithic: Evidence from Theopetra Cave - Kyparissi-Apostolika, Nina (Journal of Greek Archaeology, 2021)
The Mesolithic from Theopetra Cave was initially presented at the 1st Prehistoric Conference held in Kastoria in 1998, and later in 2000 in Documenta Praehistorica and the volume edited by Galanidou and Perlès (2003). Since then, new evidence was produced during the technical works carried out for the development and promotion of the cave (2005–2008), which provided the opportunity to carry out further excavation. Almost two decades later, this paper sets out to, if not provide definite answers regarding the period in Thessaly and Greece generally, at least to contribute to the discussion by presenting new evidence from Theopetra Cave. During these years, apart from our additional excavations, more Mesolithic sites were investigated, mainly on the Aegean islands, including Cyclope Cave on Youra, Maroulas on Kynthos, Kerame on Ikaria, as well as those on the island of Astypalaia more recently. Additional sites from mainland Greece include Boila Rockshelter in Epirus, those in the Kopais Basin, and others in the Peloponnese, including Klissoura Cave I and in the Kandia area of the Argolid. The presence of Mesolithic sites on the islands refutes models of the period that had been presented in the literature during previous decades. At this point, it is worth reiterating the following comment made by Demetrios Theocharis in 1967. There are not enough reasons to explain the disappearance of Palaeolithic populations at the end of the Pleistocene and it seems irrational to assume that adaptation here was more difficult than anywhere else. He concludes by saying that if there is any hope of finding the period that connects the Palaeolithic with the Neolithic, we need to undertake more research in caves.